2014
DOI: 10.1186/1472-6963-14-s1-s6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to investigate effects of enhanced supervision on primary eye care services at health centres in Kenya, Malawi and Tanzania

Abstract: BackgroundKnowledge and skills of primary health care workers (PHCWs) in primary eye care have been demonstrated to be inadequate in several districts of Kenya, Malawi, and Tanzania. We tested whether enhanced supervision, focused on improving practical skills over two years, would raise the scores of these workers on a test of basic knowledge and skills.MethodsThis was a randomised controlled trial. All primary health care (PHC) facilities within two districts of each country were enrolled and randomly assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…The evidence from the qualitative interviews also suggest that the four day training conducted in this setting was more effective in raising awareness of eye health than imparting skills in clinical management. This finding is consistent with evidence from earlier research in Tanzania and other settings in Africa, which showed that no more than two thirds of PHWs trained in PEC could identify cataract in pictures [ 12 ] and the PHWs’ ability and willingness to measure visual acuity, remove foreign bodies or accurately differentiate the causes of a red eye did not change after training [ 22 ]. Whether the knowledge and skills acquired during training will be translated into action in the long term will depend on overcoming the multiple barriers to this process [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…The evidence from the qualitative interviews also suggest that the four day training conducted in this setting was more effective in raising awareness of eye health than imparting skills in clinical management. This finding is consistent with evidence from earlier research in Tanzania and other settings in Africa, which showed that no more than two thirds of PHWs trained in PEC could identify cataract in pictures [ 12 ] and the PHWs’ ability and willingness to measure visual acuity, remove foreign bodies or accurately differentiate the causes of a red eye did not change after training [ 22 ]. Whether the knowledge and skills acquired during training will be translated into action in the long term will depend on overcoming the multiple barriers to this process [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Qualitative findings from a systematic review of lay health worker programmes suggest that supervisors often lack supervisory skills and face constraints due to time and transportation [ 20 ]. A randomized control trial of an enhanced supervision programme for eye care in three sub-Saharan African countries, including Tanzania, found only modest improvements in the skills and knowledge of health workers receiving enhanced supervision, with authors concluding that the lack of programme impact may be linked to poor health system functioning and high staff turnover [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed the study team to identify recurring themes and describe the salient issues that emerged from the data. NVivo 10 Software was used to store and analyse the data [ 16 ].…”
Section: Methodsmentioning
confidence: 99%